Academic anxiety as a predictor of drug abuse tendencies mediated by peer conformity - Agustin, Fenni; Ajicandra, Tifani Zafirah; Huda, Selvia Nur; Afniar, Afniar; Hapsari, Dania Prima; Sulaiman, Ahmad (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2025)
This Drug abuse among college students is a serious problem that is influenced by various psychological and social factors, including academic anxiety and peer conformity. This study aims to investigate the influence of academic anxiety on drug abuse tendencies by examining the mediating role of peer conformity. This study used a correlational type quantitative approach. The research subjects consisted of 349 college students aged 18 to 25 years old who were selected by accidental sampling technique. The measuring instruments used include multidimensional test anxiety scale to measure academic anxiety, peer pressure inventory to measure peer conformity, and substance use risk profile scale to measure drug abuse tendency. The mediation analysis showed that academic anxiety has a significant influence on drug abuse tendency, both directly (ß = 0.270; p < 0.001) and indirectly through peer conformity (ß = 0.128; p < 0.001). Thus, peer conformity partially mediated this effect. These findings support Problem-Behavior Theory, which emphasizes the importance of the interaction between internal pressure and social influence on negative behaviors Keywords: Academic anxiety; Peer conformity; Drug abuse tendency; University students. Copyright ©2025. The Authors. Published by Psikoislamika: Jurnal Psikologi dan Psikologi Islam. This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0